2002
DOI: 10.1128/jvi.76.5.2551-2556.2002
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Viral Bcl-2 Encoded by Kaposi's Sarcoma-Associated Herpesvirus and Human Bcl-2 in Primary Effusion Lymphoma Cells and Kaposi's Sarcoma Lesions

Abstract: Expression of human herpesvirus 8 viral Bcl-2 protein was demonstrated in spindle cells of late-stage Kaposi's sarcoma lesions but not in primary effusion lymphoma cell lines. In contrast, strong expression of human Bcl-2 was found in stimulated primary effusion lymphoma cells, whereas in Kaposi's sarcoma lesions preferential mononuclear cells, and to a lesser extent spindle cells, stained positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…Further incubation of this blot with antibodies to the lytic gene products ORF45 and ORF65 and to GFP revealed the similar expression of these proteins following lytic induction, suggesting that the efficiency of lytic reactivation of BAC16-mCherry-vBcl-2 is similar to that of wild-type BAC16. Of note, previous studies by others (34) and by our group (data not shown) failed to identify the expression of vBcl-2 protein in cultivated cells, and to the best of our knowledge, the present study is the first to detect endoge- (Fig. 3).…”
Section: Construction Of Bac16-vbcl-2-stopmentioning
confidence: 56%
See 2 more Smart Citations
“…Further incubation of this blot with antibodies to the lytic gene products ORF45 and ORF65 and to GFP revealed the similar expression of these proteins following lytic induction, suggesting that the efficiency of lytic reactivation of BAC16-mCherry-vBcl-2 is similar to that of wild-type BAC16. Of note, previous studies by others (34) and by our group (data not shown) failed to identify the expression of vBcl-2 protein in cultivated cells, and to the best of our knowledge, the present study is the first to detect endoge- (Fig. 3).…”
Section: Construction Of Bac16-vbcl-2-stopmentioning
confidence: 56%
“…In contrast to the levels of expression of mCherry-tagged ORF45 and of mCherry protein, which was expressed under the control of the same transcriptional control element as mCherry-vBcl-2, the level of vBcl-2 expression was low. This may account for the inability to detect the expression of vBcl-2 in KSHV-infected cell lines by using polyclonal antibodies produced by other groups (34) and in our lab (data not shown). This, together with the abundant cleavage of mCherryvBcl-2, did not allow the use of immunofluorescence to track the expression of mCherry-vBcl-2 within cells.…”
Section: Construction Of Bac16-vbcl-2-stopmentioning
confidence: 60%
See 1 more Smart Citation
“…It is expressed in a lytic pattern in spindle cells and monocytes in KS lesions, and its transcript is lytically induced in PEL cells (Fig. 1), although the protein has evaded easy detection there (98,446,533). As predicted by sequence homology, vBcl-2 is antiapoptotic; unlike its cellular counterpart, it can inhibit apoptosis induced by KSHV vCyc in the presence of high cdk6 (378).…”
Section: Orf16/vbcl-2mentioning
confidence: 99%
“…Whether the function of KS-Bcl-2 is necessary for KSHV-mediated oncogenesis is still unknown. Nevertheless, the KS-Bcl-2 protein is expressed in late-stage KS lesions but has not been detected in latent or in lytic KSHV-infected PEL cells (39).…”
mentioning
confidence: 99%